Control of a micro-forging system - Loh, Patrick Jin Kun. (2013)
Micro forging enable us to save cost and at the same time increases productivity, but as the forged material gets smaller it is inevitable to face problem such as size effect and also the struggle to keep surface roughness at a constant. Therefore in this project a piezoelectric actuator was selected as it provides features such as, high torque, precise positioning up to sub-nanometer, high stroke frequency, high resolution and repeatability.